Exploring Religious Harmony Through Dalihan Na Tolu: Local Wisdom in Peacebuilding in Indonesia - Erawadi, Erawadi; Setiadi, Fadlan Masykura (Jurnal Ilmiah Peuradeun, 2024)
This study aimed to investigate the dynamics of religious harmony and the strategies employed by Muslims and Christians in Mandailing Natal to build cohesive relationships through the indigenous cultural framework known as Dalihan Na Tolu. This study employed a qualitative descriptive method. Data collection was carried out through in-depth interviews, participant observation, and a literature review. Data analysis followed the Miles and Huberman model, which includes data presentation, data reduction, and conclusion drawing. The findings showed that the Muslim and Christian communities worked together to build peace and nurture religious harmony in Mandailing Natal. The cultural practice of Dalihan Na Tolu has long served as a foundation for accommodating the multicultural Mandailing society in fostering religious harmony and peace. The role of Dalihan Na Tolu could be seen in three aspects: socio-religious, economic, and customary practices. In these aspects, Muslims and Christians respected each other, fostered cooperation (gotong royong), and adopted a moderate and inclusive attitude towards diversity in their daily lives. Maintaining interfaith harmony through the cultural practice of Dalihan Na Tolu in Mandailing Natal is a crucial social modality that can contribute to peacebuilding and serve as a relevant strategy for preserving religious harmony in multicultural societies.